Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kompetensi Pedagogik Guru - Wakidi, Wakidi; Aristiati, Fatimah (CV. Creative Tugu Pena, 2022)
So far, the quality of human resources in the delivery of education is still felt, this is indicated by low teacher performance, teachers who lack mastery of teacher competencies, especially teacher pedagogic competencies, and the teaching methods used by teachers have not varied. Conditions like this should not be allowed to continue, because it will harm the entire community and the nation's children. By increasing the quality of education, the quality of the best graduates in education will also increase. So the role of the school principal is very active in improving a teacher's competence, so that the quality of education is no longer in the spotlight. This type of research used qualitative research to determine the Role of Principal Leadership in Improving Teacher Pedagogical Competence at Baradatu 1 Public Middle School. Qualitative research is a type of research in which the discovery procedure is carried out without using statistical or quantification procedures. In this study to obtain the right data and information, the researchers used several techniques in data collection, namely interviews, observation, and documentation. To achieve trustworthiness, credibility, transferability, dependability, and confirmability techniques related to the data collection and analysis process are used. Based on the results of the study, the strategy applied by the principal in improving the pedagogic competence of teachers at Baradatu 1 Public Middle School was to use the facility strategy. Where this strategy is more directed to the needs of teachers in the form of training or seminars, communication, and MGMP. The principal's strategy plays a very important role in improving teacher pedagogical competence so that the success of the teaching and learning process in schools can be achieved properly through the training held for teachers. Keywords: Principal Leadership, Teacher Pedagogic Competence, Pedagogic Competence